The Challenges of Crisis Response of the Franco-German Tandem after 2022 - A. P. Sokolov (Сравнительная политика)
The escalation of the Ukrainian crisis in February 2022 marked a new series of challenges for all key actors in international relations, including the states of the European Union. The largest EU countries France and Germany faced with a set of external and internal crisis phenomena chose different ways to build a strategy to overcome them. The German leadership attempted to use the Ukrainian crisis as a reason for launching previously postponed reforms in Germany and as a source of explanation for economic and social difficulties. Rising inflation, a reduction in industrial production from expensive energy resources, difficulties in migration policy and other problems were explained by Berlin as part of the price for the necessary support for Ukraine. At the same time, the reform of the Bundeswehr, which initially received broad public approval against the backdrop of the start of the Special military operation, faced criticism due to the half-heartedness of the proposed measures. As a result, the German government faced an unprecedentedly low approval rating for its performance, which only exacerbated Germany’s overall state of crisis. On the contrary, the French leadership, faced with a series of internal crises, the central plot of which was pension reform, chose not to tie them to the foreign policy dimension and, in particular, to the events in Ukraine. As a result, the French domestic political discussion did not become dependent on the logic of the development of the situation in Ukraine and was not radicalized at the expense of external participants. The difference in the choice of anti-crisis strategy has strengthened the contradictions within the Franco-German tandem as the economic and political core of the European Union.